2007
DOI: 10.1007/s11095-007-9252-1
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Visualization of Pharmacokinetics, Biodistribution and Tumor Targeting of Poly[N-(2-hydroxypropyl)methacrylamide] in Mice Using Contrast Enhanced MRI

Abstract: Contrast enhanced MRI is an effective method for non-invasive visualization of in vivo properties of the paramagnetically labeled polymer conjugates in preclinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…Three-dimensional high-resolution dynamic contrast enhanced MRI is effective for noninvasive visualization of the real-time pharmacokinetics and biodistribution of the polymer conjugates in mouse tumor models (31)(32)(33). The MRI study revealed that PGA-(Gd-DO3A)-Mce 6 resulted in relatively short blood circulation and high liver uptake possibly due to the hydrophobic interaction of mesochlorin e 6 with the reticuloendothelial system.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional high-resolution dynamic contrast enhanced MRI is effective for noninvasive visualization of the real-time pharmacokinetics and biodistribution of the polymer conjugates in mouse tumor models (31)(32)(33). The MRI study revealed that PGA-(Gd-DO3A)-Mce 6 resulted in relatively short blood circulation and high liver uptake possibly due to the hydrophobic interaction of mesochlorin e 6 with the reticuloendothelial system.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis on 2D spin-echo MR images of the tumor tissues showed that significant contrast enhancement was first observed at the tumor periphery post injection for all conjugates, and then gradually in the tumor interstitium, indicating that the distribution of the conjugates started at the tumor periphery and gradually diffused in the inner tumor tissue [27]. The 28-kDa conjugate had a short blood circulation time and its accumulation was limited to the tumor periphery.…”
Section: Mr Imaging Of Phpma-gflg-(gd-do3a) Conjugatesmentioning
confidence: 93%
“…Figure 1 shows that the pharmacokinetics of polymeric MRI contrast agents can be visualized by contrast enhanced MRI, which may also have a potential for noninvasive evaluation of pharmacokinetics of polymer drug conjugates. We have labeled N-(2-hydroxypropyl) methacrylamide copolymers (PHPMA) and poly(L-glutamic acid), two of the commonly used carriers for drug delivery, with a stable MRI contrast agent Gd-DO3A to explore the potential [27,28]. The structures of the conjugates are shown in Figure 2 and their physico-chemical characteristics are listed in Table 1.…”
Section: Non-invasive Visualization Of In Vivo Drug Delivery Of Polymmentioning
confidence: 99%
“…The macromolecule or nanoparticulate MR contrast agents exhibited higher relaxivity owing to the slow tumbling of the macromolecules compared with that of low-molecularweight chelates. 2,48) In the in vivo MRI study, signal enhancement of T 1 -weighted images of the tumor area was observed 24 h after both NP and F(5000)-NP injection. Therefore, signal enhancement in tumor tissue would be facilitated by the high Gd concentration delivered by NPs to the tumor tissue.…”
Section: Discussionmentioning
confidence: 99%